ANALYSIS OF THE INFLUENCE OF VILLAGE ORIGINAL INCOME, VILLAGE FUNDS AND RETRIBUTION TAX SHARING ON VILLAGE EXPENDITURES IN THE GIRIWOYO SUB-DISTRICT, WONOGIRI DISTRICT, 2019-2022 - Muhammad Fatikh; Suprihati Suprihati; Muhammad Hasan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the effect of Village Original Income, Village Funds and Revenue Sharing Tax Retribution on Village Expenditure in the Region of Gririwoyo District, Wonogiri Regency in 2019-2022. This research uses quantitative research with secondary data. Data collection techniques use data collection from library studies and documentation studies, document reports on the realization of the 2019-2022 APBDes. The population was obtained from villages throughout the Giriwoyo District. The sampling technique uses saturated sampling technique. The sample used in this study is the Village Government in the Giriwoyo District area consisting of 14 Villages for 4 years, the period 2019-2022. Totaling 54 samples. Data analysis used to process research data is descriptive statistical analysis, validity test, reliability test, classic assumption test using normality test, multicollinearity test, and autocorrelation test. Testing the hypothesis using multiple linear analysis, F test, t test, and test the coefficient of determination (R2). The results of data processing using SPSS show that testing the regression model with the F test is feasible to use in this study. Then partially Original Village Income has a positive and significant effect on Village Expenditures. Village Funds have a positive and significant effect on Village Expenditures. Profit Sharing Taxes and Levies have a positive and significant effect on Village Spending. Keywords: Village Original Income, Village Fund, Tax and Retribution Sharing, Village Expenditures.